The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18831/djmaths.org/2018021006
|View full text |Cite
|
Sign up to set email alerts
|

A Distribution-Free Model with Variable Setup Cost, Backorder Price Discount and Controllable Lead Time

Abstract: The purpose of this study is to investigate an inventory model for variable setup cost under stochastic conditions, in which the order quantity, reorder point, lead time and backorder price-discount rate are decision variables. The lead time demand is stochastic and exact distribution is unknown. Therefore, the distributionfree approach for the lead time demand with known mean and standard deviation is discussed. The proposed method is validated based on the numerical example and sensitivity analysis, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Shin et al [47] extended the continuous review model with transportation discounts and demand fill-rate. Malik and Sarkar [48] studied the inventory model for a distribution-free approach with controllable lead time, variable setup cost, and backorder price discounts. Further, studies in this direction can be found in Malik and Sarkar [49], Moon et al [50], and Guchhait et al [51].…”
Section: Scm With Vendor-buyer Coordination Policymentioning
confidence: 99%
“…Shin et al [47] extended the continuous review model with transportation discounts and demand fill-rate. Malik and Sarkar [48] studied the inventory model for a distribution-free approach with controllable lead time, variable setup cost, and backorder price discounts. Further, studies in this direction can be found in Malik and Sarkar [49], Moon et al [50], and Guchhait et al [51].…”
Section: Scm With Vendor-buyer Coordination Policymentioning
confidence: 99%
“…Furthermore, Malik and Sarkar [8] studied a continuous-review policy for multiple products with uncertain demand, investments for quality improvements and setup cost reduction, and lead-time control with unknown lead-time demand distribution. Malik and Sarkar [9] recently presented a backorder price discount model with controllable lead time and unknown distribution for lead-time demands. A recent study in a similar direction can be found in Dey et al [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, researchers adopted a distribution-free approach to solve these types of problems, which is a more realistic approach [3][4][5]. It is proved from the literature that additional investments can reduce the setup cost for the production system [6][7][8][9]. Mostly, researchers consider continuous investments for controlling the setup cost; however, the discrete investment can be more realistic as the industry may not prefer continuous investment; thus, this is another research gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [30] analyzed the SC model under stochastic demands, service level constraints and lead time control with additional costs. Recently, Malik and Sarkar [31] studied the SC models while considering lead time and setup cost reductions with discrete investments. With lead time reductions, the service level can be improved, and customers' satisfaction may help management to increase their profits.…”
Section: Introductionmentioning
confidence: 99%